Development of Multi‐Catalytic Strategies Based on the Combination between Iron‐/Copper‐ and Organo‐Catalysis. Issue 5 (28th April 2020) - Quintard, Adrien
Abstract: Despite the latest advances in catalysts efficiency, using one single catalytic activation mode can lead to considerable limitations. To overcome reactivity or selectivity issues, multi‐catalytic combinations can represent interesting alternatives. This manuscript reviews the recent transformations developed in my group through the combination between cheap iron or copper complexes and organo‐catalysis. Combining these activation modes enables considerable synthetic economies inconceivable by using one single catalyst. The strategies developed to combine efficiently different catalysts as well as the resulting synthetic applications are discussed. Abstract :